(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2020)
Зима Ю.О. ОНТОЛОГІЧНІ ПЕРЕДУМОВИ РОЗВИТКУ АУТСОРСИНГУ Мета. Дослідження онтологічних передумов розвитку аутсорсингу та обґрунтування практичного інструментарію його реалізації в сучасних умовах господарювання. Методика дослідження. Методологічною основою дослідження є системний підхід до вивчення проблематики аутсорсингової діяльності. В процесі дослідження використано загальнонаукові та спеціальні методи, зокрема: еволюційний підхід і системно-аналітичний метод при обґрунтуванні онтологічних особливостей аутсорсингової діяльності та при аналізі і оцінці практичного інструментарію реалізації аутсорсингу в світі. Результати дослідження. Встановлено, що основними онтологічними передумовами розвитку аутсорсингу в світовому господарстві стали принципи поділу праці, спеціалізації та кооперації як в організації виробничої діяльності, так й в організації системи управління. Поділ праці при організації виробничої діяльності та при організації системи управління усунув всі сторонні елементи з процесу. За рахунок спеціалізації, компанії, які спеціалізуються на виконанні певного виду робіт, наданні послуг здатні повніше і якісніше задовольнити запити споживачів. Внутрішня кооперація дозволяє компанії бути більш гнучкою на ринку та швидко вносити зміни у плани виробництва та систему управління. Аргументовано, що спеціалізація на послузі забезпечує зростання якості виконуваних робіт, а економія на масштабах веде до відносного здешевлення надання послуг. Визначено, що екстерналізація послуг дозволяє, за рахунок спеціалізації, економії ресурсів розширювати набір суміжних послуг та лінійно їх деверсифікувати. Наукова новизна результатів дослідження. Доведено, що в основу аутсорсингу покладено поділ праці при виробництві продукції. Встановлено, що елементи аутсорсингу постійно еволюціонують і обумовлюють появу нових форм організації ринку і моделей господарювання. Обґрунтовано, що аутсорсинг об’єднує переваги спеціалізації і поділу праці у виробництві, переваги поділу відповідальності і повноважень в управлінні, які забезпечують ефективну організацію виробничої системи в умовах зростаючої конкуренції. Аргументовано, що аутсорсинг може виникнути у всіх формах, видах і підвидах поділу праці: від технічного на підприємстві, коли виробничі процеси передаються аутсорсинговим компаніям, до міжнародного, – коли аутсорсингові компанії діють на міжнародних ринках. Встановлено, що сучасні технології, особливо інформаційні, допускають небачені раніше варіанти поділу праці, а аутсорсинг виступає і як інструмент, що поглиблює поділ праці, і одночасно як інструмент кооперації праці. Аутсорсинг в умовах сьогодення виступає ефективним інструментом поділу праці та розподілу як процесу виробництва так й самого процесу управління, що посилює економічний ефект від його застосування. Практична значущість результатів дослідження. Теоретичні та методологічні положення поглиблюють практичні засади забезпечення розвитку аутсорсингу в національній економіці та сприятимуть активізації модернізаційних перетворень національного господарства. Ключові слова: аутсорсинг; виробництво; поділ праці; спеціалізація; кооперація. Зима Ю.А. ОНТОЛОГИЧЕСКИЕ ПРЕДПОСЫЛКИ РАЗВИТИЯ АУТСОРСИНГА Цель. Исследование онтологических предпосылок развития аутсорсинга и обоснование практического инструментария его реализации в современных условиях хозяйствования. Методика исследования. Методологической основой исследования является системный подход к изучению проблематики аутсорсинговой деятельности. В процессе исследования использованы общенаучные и специальные методы, в частности: эволюционный подход и системно-аналитический метод при обосновании онтологических особенностей аутсорсинговой деятельности и при анализе и оценке практического инструментария реализации аутсорсинга в мире. Результаты исследования. Установлено, что основными онтологическими предпосылками развития аутсорсинга в мировом хозяйстве стали принципы разделения труда, специализации и кооперации как в организации производственной деятельности, так и в организации системы управления. Разделение труда при организации производственной деятельности и при организации системы управления устранило все посторонние элементы из процесса. За счет специализации, компании, специализирующиеся на выполнении определенного вида работ и оказании услуг, способны полнее и качественнее удовлетворить запросы потребителей. Внутренняя кооперация позволяет компании быть более гибкой на рынке и быстро вносить изменения в планы производства и систему управления. Аргументировано, что специализация на услуге обеспечивает рост качества выполняемых работ, а экономия на масштабах ведет к относительному удешевлению предоставления услуг. Определено, что экстернализация услуг позволяет, за счет специализации и экономии ресурсов, расширять набор смежных услуг линейно их диверсифицировать. Научная новизна результатов исследования. Доказано, что в основу аутсорсинга положено разделение труда при производстве продукции. Установлено, что элементы аутсорсинга постоянно эволюционируют и обусловливают появление новых форм организации рынка и моделей хозяйствования. Обосновано, что аутсорсинг объединяет преимущества специализации и разделения труда в производстве, преимущества разделения ответственности и полномочий в управлении, которые обеспечивают эффективную организацию производственной системы в условиях растущей конкуренции. Аргументировано, что аутсорсинг может возникнуть во всех формах, видах и подвидах разделения труда: от производственного на предприятии, когда производственные процессы передаются аутсорсинговым компаниям, к международному, – когда аутсорсинговые компании действуют на международных рынках. Установлено, что современные технологии, особенно информационные, допускают невиданные ранее варианты разделения труда, а аутсорсинг выступает и как инструмент, который углубляет разделение труда, и, одновременно, как инструмент кооперации труда. Аутсорсинг в сегодняшних условиях выступает эффективным инструментом разделения труда и распределения как процесса производства, так и самого процесса управления, который усиливает экономический эффект от его применения. Практическая значимость результатов исследования. Теоретические и методологические положения углубляют практические основы обеспечения развития аутсорсинга в национальной экономике и будут способствовать активизации модернизационных преобразований национального хозяйства. Ключевые слова: аутсорсинг; производство; разделение труда; специализация; кооперация. Zyma Yu.O. ONTOLOGICAL PRECONDITIONS FOR OUTSOURCING DEVELOPMENT Purpose. The purpose of the article is a research of ontological preconditions for outsourcing development and foundation of practical tools for its implementation in modern economic conditions. Methodology of research. The theoretical and methodological basis of the study is a systematic approach to the research of outsourcing activities. General scientific and special methods are applied in the process of research, in particular: evolutionary approach and system analysis method are applied for explanation of ontological peculiarities of outsourcing activity and for the analysis and evaluation of practical tools for outsourcing implementation in the world. Findings. It is established that the main ontological preconditions for the development of outsourcing in the world economy are the principles of division of labour, specialization and cooperation both in the organization of production activities and in the organization of the management system. The division of labour within the organization of production activities and within the organization of management system has eliminated all the external elements of the process. By virtue of specialization, companies that specialize on particular type of works or services are able to meet consumer inquiries more fully and satisfactorily. Internal cooperation allows a company to be more flexible on the market and quickly make changes to production plans and management system. It was reasoned that service specialization ensures an increase in the quality of the works performed, and economies of scale leads to a relative reduction in the cost of services provision. It is determined that externalization of services allows, at the expense of specialization and economy of resources, to expand a set of related services and to diversify them linearly. Originality. It is proved that the basis of outsourcing is the division of labour within the production. It has been established that the elements of outsourcing are constantly evolving and cause the emergence of new forms of market organization and management models. It is demonstrated that outsourcing combines the advantages of specialization and division of labour in production, the advantages of division of responsibility and authority in management, which ensures the effective organization of the production system in the context of increasing competition. It was argued that outsourcing can occur in all forms, types and subtypes of division of labour: from the technical one at the enterprise, when the production processes are transferred to outsourcing companies, to the international one, when outsourcing companies operate in international markets. It was established that modern technologies, especially information ones, allow for unprecedented variants of division of labour, and outsourcing acts as a tool that deepens the division of labour and, at the same time, as a tool of cooperation of labour. Outsourcing, in today’s conditions, is an effective tool for the division of labour and the distribution both of the production process and the management process, which enhances the economic effect of its application. Practical value. Theoretical and methodological provisions deepen the practical principles for the development of outsourcing in the national economy and promote the intensification of modernization reforms of the national economy. Key words: outsourcing; production; division of labour; specialization; cooperation.